2014
DOI: 10.1212/wnl.0000000000000494
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Neuro Images : “Mini brain” sign

Abstract: A 41-year-old woman presented with refractory low back pain for the last 6 months. Neurologic examination was normal. Blood tests showed high erythrocyte sedimentation rate. A spine MRI (figure 1) disclosed involvement of the T12 vertebral body. There was hyperintense signal in T2-weighted sequence and multiple linear hypointense areas with cortical and radiated pattern resembling the brain parenchyma (the "mini brain" sign) (figure 2). Biopsy confirmed solitary plasmacytoma. Mini brain sign represents cortica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
(2 reference statements)
0
6
0
Order By: Relevance
“…A "spoke-wheel" pattern has also been described. [6][7][8][9][10][11][12] The characteristic appearance of thickened cortical struts may be due to chronic bone marrow compromise by disease with secondary compensation of bone strengthening in the cortical layer. This phenomenon is also described in Paget´s disease and hemangiomas, however in these cases, the "mini brain" pattern is not seen.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A "spoke-wheel" pattern has also been described. [6][7][8][9][10][11][12] The characteristic appearance of thickened cortical struts may be due to chronic bone marrow compromise by disease with secondary compensation of bone strengthening in the cortical layer. This phenomenon is also described in Paget´s disease and hemangiomas, however in these cases, the "mini brain" pattern is not seen.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 12, only six were specific for radiological image patterns for MM/plasmocytoma. [6][7][8][9][10][11][12] Sha et al reported a characteristic appearance in four cases out of six patients with plasmacytoma. MRI features were curvilinear areas of low signal intensity within the vertebra and/or cortical irregularity.…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations